Social studies at the center : integrating kids, content, and literacy - Lindquist, Tarry; Selwyn, Douglas, 1949-; Varner, William (Portsmouth, NH : Heinemann, 2000)
Presents a wide variety of strategies for teaching social studies to intermediate and middle school students, placing the subject at the center of the school curriculum; and includes two model units, resources, and websites.
Includes bibliographical references.
Professional
Keywords: Social sciences -- Study and teaching (Elementary) -- United States; Social sciences -- Study and teaching (Middle school) -- United States; Social sciences -- Study and teaching